2017
DOI: 10.1111/tbed.12733
|View full text |Cite
|
Sign up to set email alerts
|

Global genetic variation and transmission dynamics of H9N2 avian influenza virus

Abstract: The H9N2 influenza viruses are extensively circulating in the poultry population, and variable genotypes can be generated through mutation, recombination and reassortment, which may be better adapted to infect a new host, resist drug treatment or escape immune pressure. The LPAI H9N2 viruses have the potential to evolve towards high levels of virulence in human. Some studies about the regional dispersal were reported, but global dissemination and the drivers of the virus are poorly understood, particularly at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Previous studies have shown extensive expansions to the Middle East after its first emergence in Asia, forming a close genetic linkage between two regions (Fusaro et al, 2011;Nagy et al, 2017;Wei and Li, 2018). Furthermore, phylogenetic divergence of Asian and the Middle Eastern H9N2 viruses has also been reported through the ongoing viral evolution (Fusaro et al, 2011;Hu et al, 2017;Naguib et al, 2017;Wei and Li, 2018). Together, these finding indicated that Asia served as the original transmission source of global H9N2 viruses, but our analyses give heighten the distinct role of Middle East as transmission hub in shaping the following spatial expansions.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Previous studies have shown extensive expansions to the Middle East after its first emergence in Asia, forming a close genetic linkage between two regions (Fusaro et al, 2011;Nagy et al, 2017;Wei and Li, 2018). Furthermore, phylogenetic divergence of Asian and the Middle Eastern H9N2 viruses has also been reported through the ongoing viral evolution (Fusaro et al, 2011;Hu et al, 2017;Naguib et al, 2017;Wei and Li, 2018). Together, these finding indicated that Asia served as the original transmission source of global H9N2 viruses, but our analyses give heighten the distinct role of Middle East as transmission hub in shaping the following spatial expansions.…”
Section: Discussionsupporting
confidence: 56%
“…However, although we have subsampled all of the available H9N2 HA genetic diversity, it is important to note that reporting LPAIVs H9N2 varies between different countries our analysis is just reflecting the currently available data. Previous studies have shown extensive expansions to the Middle East after its first emergence in Asia, forming a close genetic linkage between two regions (Fusaro et al, 2011;Nagy et al, 2017;Wei and Li, 2018). Furthermore, phylogenetic divergence of Asian and the Middle Eastern H9N2 viruses has also been reported through the ongoing viral evolution (Fusaro et al, 2011;Hu et al, 2017;Naguib et al, 2017;Wei and Li, 2018).…”
Section: Discussionmentioning
confidence: 96%
“…This allows the simultaneous inference of viral transition rates among specified traits (i.e., hosts or locations) and their association with covariates that may drive viral movement. This approach has been adapted to investigate the role of anthropogenic and environmental variables on the diffusion of avian influenza within China (17) as well as of avian influenza subtype H9N2 on a global scale (18). The GLM has also been used to uncover the impact of host behavior on the dispersal of rabies virus among bat species (19).…”
Section: Introductionmentioning
confidence: 99%
“…H9N2 has become the most prevalent subtype of low pathogenic avian influenza in poultry. After introduction to Eurasian poultry, this virus has diverged into five genetic lineages: G1, Y280, BJ94, G9, and Y439/Korea lineage [2] and has become endemic in poultry across Asia, the Middle East, and North Africa [3].…”
Section: Introductionmentioning
confidence: 99%